2012
DOI: 10.1111/j.1365-2834.2012.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' perceptions of conditions for patient education - focusing on organisational, environmental and professional cooperation aspects

Abstract: Managerial support for the development of visible patient education routines (e.g. allocation of time, place and guidelines) is required. One recommendation is to designate a person to oversee educational work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…Lack of knowledge has been identified as a barrier to the implementation of patient education [18] and a lack of resources, structured training, and skills development is considered a barrier to the implementation of CHD secondary prevention [22]. It is therefore concerning that in previous studies, nurses have reported their inactivity in reading literature related to patient education and failure to follow the development of knowledge in those areas [32]. Reluctance to conduct patient education and lack of knowledge in this area are issues that must clearly be addressed if health professionals are to improve their competencies in patient education.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge has been identified as a barrier to the implementation of patient education [18] and a lack of resources, structured training, and skills development is considered a barrier to the implementation of CHD secondary prevention [22]. It is therefore concerning that in previous studies, nurses have reported their inactivity in reading literature related to patient education and failure to follow the development of knowledge in those areas [32]. Reluctance to conduct patient education and lack of knowledge in this area are issues that must clearly be addressed if health professionals are to improve their competencies in patient education.…”
Section: Discussionmentioning
confidence: 99%
“…8 Because contextual and country-specific factors may influence the implementation of PE, it is important to study facilitators and barriers to PE specific to the Iranian context. 6,11,12 So the aim of the current study was to presents a comprehensive review of the literatures, exploring barriers and facilitators of PE among Iranian nurses, in order to identify strategies to promote enhanced PE within the Iranian healthcare system context.…”
Section: Introductionmentioning
confidence: 99%
“…These include work overload and time pressure, [5,20,21] difficulty in communication with patients, [16,20] lack of educational resources, [22] insufficient knowledge and skills, [5,[20][21][22][23] limited managerial support, [24] low priority given to patient education, [25,26] and inappropriate organizational culture. [27,28] However, to the best of our knowledge, previous studies did not associate these hindering factors to a comprehensive theoretical framework.…”
Section: Introductionmentioning
confidence: 99%